Pengaruh Tingkat Vakum dan Metode Pasteurisasi terhadap Mutu Nasi Kemas - Bovi Wira Harsanto (Jurnal BETAHPA, 2022)
Rice is one of the staple foods of Indonesian people. Age keeps the rice short enough and the serving takes a long time to be a barrier for Indonesian people in consuming rice in all situations, especially emergencies. Making rice with special treatment, such as vacuum packaging and pasteurization is expected to overcome these problems. This rice product is called packaged rice. This study aimed to determine the level of vacuum and the suitable pasteurization method in the manufacture of packaged rice products. Vacuum packing followed by pasteurization (steaming and boiling) is the method of choice to produce packaged rice. The results showed that the vacuum level and pasteurization were not able to produce packaged rice that had a long shelf life, especially when stored at room temperature. This is indicated by the total results of microbes that exceed the safe limit, which is > 6 logs CFU/gram. The results of the total microbes affected the decrease of pH on days 4 and 7, and also the results of sensory evaluation on days 4 and 7, which was not suitable for testing to the panelists. However, cold storage has a better effect in terms of the shelf life of packaged rice products because the rate of microbial growth is inhibited so that the total microbial count is < 6 logs CFU/gram. Therefore, packaged rice products are recommended to be stored at cold temperatures before being consumed.